Desafíos para la filosofía del derecho del Siglo XXI - Ródenas, Ángeles (2017)
This paper shows a mismatch between a real and pressing demand for a philosophical analysis that allows us to explain the emergence of new phenomena in law, and the limited supply of theoretical tools to satisfy this demand by the traditional model of positivistic science of law. After an initial diagnosis of a mismatch between supply and demand, the resistance of legal positivism to accept practical rationality stands out as a core problem of the traditional model of positivistic science of law and the viability of this way of rationality is defended. The paper concludes with a proposal for the reinvention of the philosophy of law of the 21st century that incorporates new objectives and rethinks its method.